Differences in Fatty Acid Profiles, ADEK Vitamins and Sterols of the Yolk between Native Chickens and Geese - Kalaycı, Serpil; Yılmaz, Ökkeş (Zonguldak Bülent Ecevit Üniversitesi, 2011)
The aim of this study was to assess the differences in the yolk lipid composition of geese and chickens which are free to select their diets from the environments. The proportion of oleic acid 18:1n-9 and linolenic acid 18:3n-3 was far greater in both of species of yolk lipids. In particular, the proportion of docosahexaenoic acid in the total lipid of the yolk was greater for the chicken compared to the geese. By contrast, the proportion of arachidonic acid in total yolk lipid was approximately two times greater for the goose than the chicken. Thus the chicken was more efficient at incorporating long-chain C22 fatty acid of the n-3 series into yolk lipid whereas the geese incorporated C20 fatty acid of the n-6 series. The ADEK vitamins of the goose egg in mg/g yolk were very similar to that of the chicken egg. The cholesterol content of the geese egg in mg/g yolk was far greater to that of the chicken egg.